Responsible Return to Work: A Case Study of Workers with Acquired Disability in Remote Plantations - Riani Rachmawati; As Syahidah Al Haq; Nadia Karina Hakman; Muthia Pramesti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines how return-to-work practices are implemented for workers with acquired disabilities following work-related accidents in a remote plantation setting in Indonesia. It explores how return-to-work responsibility is enacted at the workplace level and whether existing practices align with the principles of responsible return to work in labor-intensive, geographically isolated settings. Using a qualitative case study approach, the research draws on in-depth interviews with injured workers and organizational actors, supported by workplace observations. Data were analyzed thematically using the responsible return to work framework, which encompasses legal, economic, moral, and discretionary dimensions. The findings show that return-to-work is primarily implemented as employment retention rather than meaningful reintegration. Legal and economic responsibilities emphasize procedural compliance and income continuity, while moral responsibility is framed through organizational care that often takes a paternalistic form. Discretionary responsibility is largely exercised by supervisors, leading to uneven outcomes shaped by managerial judgment and operational constraints. The study positions return-to-work as an organizational and industrial relations process influenced by power dynamics and contextual limitations, demonstrating how fragmented responsibility constrains dignity, participation, and sustainable work trajectories.